Secularization in Ireland: Analyzing the Relationship between Religiosity and Demographic Variables in Ireland from the European Social Survey 2002-2012 - Breen, Michael J. (The international journal of religion and spirituality in society, 2014)
The European Social Survey (the ESS) is an academically-driven social survey designed to chart and explain the interaction between Europe's changing institutions and the attitudes, beliefs and behavior patterns of its diverse populations. The core elements are Trust in Institutions; National, Ethnic, and Religious Identity; Political Engagement; Well-being, Health and Security; Socio-political Values; Demographic Composition; Moral and Social Values; Education and Occupation; Social Capital; Financial Circumstances; Social Exclusion; and Household Circumstances. This research includes five rounds of data from 2002 to 2012.